Universo Bali. Danza y audiovisual - Rubin, María José (Imagofagia, 2021)
Sobre Alejandra Torres (ed.). Universo Bali. Danza y audiovisual. Buenos Aires: edición de la autora, 2018, 286 pp., ISBN: 978-987-42-8515-7.